2018
DOI: 10.1016/j.eclinm.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of Measles Vaccination in HIV-Infected and HIV-Exposed Uninfected Children: A Systematic Review and Meta-Analysis

Abstract: Background HIV-infected and HIV-exposed uninfected (HEU) children have an increased risk of measles that may be due to altered immune responses or suboptimal timing of measles vaccination. We aimed to evaluate the safety and immunogenicity of measles vaccination in HIV-infected and HEU children. Methods For this systematic review and meta-analysis, we searched PubMed, Embase, Cochrane Library, CINAHL, Global Health Library and IndMED on May 9, 2018. Studies were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 89 publications
(154 reference statements)
1
13
0
1
Order By: Relevance
“…These conditions raise the risk of sudden outbreaks of vaccine-preventable diseases occurring when social distancing restrictions are eased. For children who already have a compromised immune system (e.g., those living with HIV), likelihood of mortality from vaccinepreventable conditions (e.g., measles) is higher if immunizations are not received (10).…”
Section: Disruptions To Immunization Programsmentioning
confidence: 99%
“…These conditions raise the risk of sudden outbreaks of vaccine-preventable diseases occurring when social distancing restrictions are eased. For children who already have a compromised immune system (e.g., those living with HIV), likelihood of mortality from vaccinepreventable conditions (e.g., measles) is higher if immunizations are not received (10).…”
Section: Disruptions To Immunization Programsmentioning
confidence: 99%
“…As imunizações devem seguir o calendário vacinal de crianças vivendo com HIV, até definição da sua condição sorológica (3,(4)(5) . O acompanhamento recomendado em Serviço de Assistência Especializada (SAE) deve contemplar as especificidades da exposição ao HIV, e ser realizado mensalmente, no primeiro semestre e, no mínimo, bimensal até confirmação sorológica.…”
Section: Introductionunclassified
“…101,102 Vaccination is therefore essential in HIV-infected patients because of the increased risk of developing various infectious diseases. 103,104 This review revealed research inequalities across the African region regarding studies on the burden of vaccine-preventable diseases among HIV-infected and HIV-exposed children. South However, the same vaccine is contraindicated in immunocompromised children who ironically are susceptible to the disease.…”
mentioning
confidence: 99%
“…Studies have also shown that there are poor immune responses to primary vaccination among HIV-infected children in comparison to HIV-unexposed and HIV-exposed children. The poor immune response among HIVinfected children may require booster doses for optimal immunity against vaccine-preventable diseases 103,104. This review revealed research inequalities across the African region regarding studies on the burden of vaccine-preventable diseases among HIV-infected and HIV-exposed children.South Africa contributed about half of the included articles with Nigeria and Kenya following with fewer studies.…”
mentioning
confidence: 99%